HYGIENIC ASSESSMENT OF ILLNESS INDICATORS OF WORKERS IN WASTE PROCESSING ENTERPRISES - Alimukhamedov D. Sh.; Kenjaev Y. M. (The Conference Hub, 2025)
Waste processing is a key element of modern societies and makes a significant contribution to environmental sustainability. However, the health of workers in waste processing enterprises is often exposed to various occupational hazards and is at risk. This scientific study analyzes the hygienic indicators of the morbidity of preventive workers as preventive measures to restore and maintain the health of workers working in a harmful environment. The study combines the scientific fields of food science, labor protection and preventive medicine, providing an integrated approach to improving the health and well-being of this important group of workers.